2009
DOI: 10.2337/dc09-0112
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in Type 1 Diabetes Is Associated With Enhanced Excretion of the Endocytic Multiligand Receptors Megalin and Cubilin

Abstract: OBJECTIVEProteinuria is the hallmark of diabetic nephropathy; yet, glomerular histology does not fully explain mechanisms contributing to proteinuria. Our objective was to identify proteins in the urine of individuals with type 1 diabetes and microalbuminuria that might implicate a mechanistic pathway operative in proteinuria.RESEARCH DESIGN AND METHODSUsing a GeLC/MS platform proteomics approach, we compared the urine proteome from 12 healthy nondiabetic individuals, 12 subjects with type 1 diabetes yet norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 14 publications
5
71
0
Order By: Relevance
“…31,32 In humans, shedding of megalin and cubilin in urine is increased in individuals with type 1 diabetes and microalbuminuria compared with nonalbuminuric controls. 33 These studies suggest that reduced expression or loss of the cubilin-megalin complex may contribute to the albuminuria of early diabetic kidney disease via reduced tubular reuptake of filtered albumin, which is supported by our observed association of rs1801239 with incident persistent microalbuminuria in the DCCT/EDIC Study.…”
Section: Discussionsupporting
confidence: 74%
“…31,32 In humans, shedding of megalin and cubilin in urine is increased in individuals with type 1 diabetes and microalbuminuria compared with nonalbuminuric controls. 33 These studies suggest that reduced expression or loss of the cubilin-megalin complex may contribute to the albuminuria of early diabetic kidney disease via reduced tubular reuptake of filtered albumin, which is supported by our observed association of rs1801239 with incident persistent microalbuminuria in the DCCT/EDIC Study.…”
Section: Discussionsupporting
confidence: 74%
“…We measured urinary albumin for two purposes. 1) albumin, like DBP, is a known ligand of megalin (30), and 2) severe albuminuria is a biological marker of nephropathy (8,30,31). We found that marked albuminuria was present in the ZDF animals, which excreted ϳ20-fold greater amounts of albumin compared with lean control animals.…”
Section: Study 1: Characterization Of Renal Vitamin D Reabsorption Inmentioning
confidence: 57%
“…In support of this concept, researchers showed that when megalin, cubilin, or Dab2 expression is absent, loss of 25D 3 -DBP in the urine was dramatically elevated and severe vitamin D deficiency resulted (21,22). Moreover, renal megalin and cubilin levels were markedly reduced in humans and rats with diabetes (30,31), which resulted in increased urinary excretion of albumin, another known ligand of megalin.…”
mentioning
confidence: 79%
“…87 Patients with type 1 diabetes and albuminuria had significantly elevated urinary levels of megalin and cubilin, suggesting possible PT shedding of these proteins as a contributing factor to albuminuria in patients with diabetes. 88 Moreover, in early streptozotocin-induced diabetes in rats, the GSC A was unchanged but PTC uptake of albumin was markedly reduced. 47 …”
Section: The Megalin-cubilin Complexmentioning
confidence: 97%